TRYPANOSOMA INFESTATIONS IN ROYAL BENGAL TIGER (PANTHERA TIGRIS TIGRIS) AT LAHORE ZOOLOGICAL GARDENS AND ITS THERAPY - B. N. Khan; Z. Ali; R. Yasmeen; F. Bibi; Ziauulah; N. Mehboob (Journal of Animal and Plant Sciences, 2015)
The aim of this study was to describe the signs and symptoms of Trypanosomiasis and its effective therapy. A large population of Royal Bengal Tigers (Panthera tigris tigris) in many zoos of the world including those in India, Bangladesh and Pakistan, have suffered a lot from this disease. The present study was conducted on three white and three brown tigers infested by Trypanosoma at Lahore Zoo. Two doses of Fa.try.banil injection (Fatro, Emilia, Italy) containing Diminazene aceturate as active ingredient, was injected at a recommended dose rate for treatment of sick animals and as prophylactic therapy to others to make possible the survival of endangered species of Royal Bengal Tigers (Panthera tigris tigris) kept in captivity. an urgent need to recognize the infectious diseases
Keywords: Royal Bengal Tigers; Trypanosoma; Diminazene aceturate; Lahore Zoo.